DAMPAK OVERALL SERVICE QUALITY DALAM MENINGKATKAN KEPUASAN PELANGGAN FASHION E-COMMERCE DI INDONESIA - Ariyani, Widitya; Rahayu, Siti; Widjaja, Fitri Novika (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
E-commerce or electronic commerce, involves the online buying and selling of goods and services, linking businesses with consumers. This study explores how various elements of fashion e-commerce service quality affect customer perceptions and satisfaction. Higher satisfaction levels in e-commerce often result in increased customer retention. Utilizing the SERVQUAL model, the research evaluated service quality by examining factors related to information and system quality. Surveys were conducted among Indonesian adults from September to October 2024, with data analyzed using SmartPLS 4.0. The results revealed significant correlations between reliability and responsiveness in fashion e-commerce service quality. Additionally, system qualities were strongly linked to overall service excellence. The findings emphasize that perceived service quality is vital for customer satisfaction and their revisit intention. Key factors influencing service quality included reliability, interactivity, and ease of use. To enhance quality perception and foster user trust, e-commerce managers should adopt advanced technologies. The study concludes with suggestions for future research.